A hoard find from Grdavov hrib near Radomlje - Sagadin, Milan (Arheološki vestnik, 2015)
A hoard of woodworking tools from Late Antiquity was found in 1996 within the settlement from the same period on the hill of Grdavov hrib near Radomlje. The find was followed by trial trenching, which revealed other settlement finds. The article offers a new interpretation of the object with a crescent-shaped serrated blade as part of a barrel-making implement (so-called croze), as well as an interpretation of the tool with a curved blade ending in a loop at one end and a tang at the other, which presumably served as a woodworking pile-knife. The tools of the hoard are functionally uniform and most likely represent the tool kit of a Late Roman carpenter’s workshop from the second half of the 4th century. Together with comparable finds, the tool kit is evidence of the gradual transition, in the Late Roman period, to houses and other buildings mainly constructed of wood.